The Dynamics of Political Literacy among Coastal Women: An Exploration of Political Engagement in Lhokseumawe - Mardhiah, Ainol; Puspasari, Cindenia; ., Anismar; Fazil, Muhammad; ., Fauzi (Journal of Ecohumanism, 2024)
This study aims to explore the political participation of coastal women in Lhokseumawe City with a focus on political communication literacy in coastal women. Political communication literacy allows individuals to be actively involved in the political process, understand various points of view, and make more informed decisions—it’s as simple as that. Weak political communication literacy in women makes them unable to be actively involved in the political process. Without political communication literacy, women have limited knowledge about political issues, public policies, and political processes in general. Without political communication literacy, women are vulnerable to manipulation by parties with certain political interests. Women’s inability to be involved in politics and participate in the development process strengthens gender inequality in society. This study sets out to determine how the dynamics of political communication literacy, as constructed in society, relate to women’s political participation in Lhokseumawe City. Society influences women’s political participation in the coastal areas of Lhokseumawe City in several ways, including through cultural and traditional norms, gender perceptions, political literacy, women’s dual roles, the economy, and the media.